Anti-Semitism in Central Europe between the World Wars : Semantics, Social Practice, Political Programme in Austria and Slovakia (with Consideration of Hungarian Connections) - Szabó, Miloslav (Díké - Journal of Dezső Márkus Research Group for Comparative Legal History, 2025)
This article analyses the most important trends in the history of anti-Semitism in Central Europe in the interwar period, with a focus on Austria and Czechoslovakia (until 1938), supplemented by Hungarian connections and an excursus into the period of the Slovakian state (1939–1945). The focus is on the areas of semantics (‘Judeo-Bolshevism’ and ambiguities of racism), social practice (Numerus Clausus and cultural ‘Judaization’) as well as political and legal programmes (‘solution to the Jewish question’ in the context of Catholicism). Additionally, the relationship between autochthonous forms of anti-Semitism and the role model function of Nazi Germany are analysed.